PENGARUH PEMAHAMAN PERPAJAKAN, INSENTIF PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL, DAN MENENGAH (Studi Pada UMKM yang Terdaftar di KPP Pratama Malang Utara) - Luis Wijaya Kusuma; Nur Diana (Universitas Islam Malang, 2022)
Micro, small and medium enterprises (MSMEs) have dominated the Indonesian economy. This business group is proven to be able to make a significant contribution. The increasing number of MSMEs from year to year provides an opportunity for the Government to target this sector to increase revenue from the tax sector. This study responds to the issue of factors that affect mandatory compliance, which consists of variables of understanding of taxes, tax incentives, and awareness of taxpayers for micro, small and medium enterprises in the KPP Pratama North Malang area. Ninety-nine respondents obtained—sampling based on purposive sampling methods. Data analysis uses a multiple linear regression model. This study indicates that Tax Understanding, Tax Incentives, and Taxpayer Awareness have a significant positive effect on Taxpayer Compliance for Micro, Small, and Medium Enterprises. Understanding Taxation has a significant positive impact on Taxpayer Compliance for Micro, Small, and Medium Enterprises. Tax incentives and Taxpayer awareness have a significant positive effect on taxpayer compliance for micro, small and medium enterprises. Keywords: Tax Understanding, Tax Incentives, Taxpayer Awareness and Taxpayer Compliance.